Performance enhancement of triboelectric nanogenerators using contact-separation mode in conjunction with the sliding mode and multifunctional application for motion monitoring. (November 2022) - Xu, Zhenyuan; Zhang, Dongzhi; Cai, Haolin; Yang, Yan; Zhang, Hao; Du, Chen
Abstract: Triboelectric nanogenerators (TENGs), which can extensively harvest environmental mechanical energy, have long been restricted by their motion patterns, surface electric charges, and other factors. In this work, a TENG that cooperates with the vertical contact separation mode TENG (CS-TENG) and the lateral sliding mode TENG (LS-TENG) is proposed. This hybrid mode TENG can effectively improve the output power of the independent mode TENG. In the experiment, CS-TENG and LS-TENG are integrated to work together. In this way, the open circuit voltage of the hybrid mode TENG is determined by the CS-TENG, and the peak-to-peak open circuit voltage of the hybrid TENG can reach 1169 V. The unidirectional short-circuit current of CS-TENG is about 80 μA. The unidirectional short-circuit current of the LS-TENG is about 27 μA. But the unidirectional short-circuit current of the hybrid TENG can reach 187 μA. The self-powered human motion sensors based on CS-TENG were designed for detecting signals of finger bending, gait and somatic joint bending. It can clearly identify the motion signals of different parts, which could provide effective information for post-rehabilitation training of patients with limb injuries, as well as smart medical care. Graphical Abstract: Exploted view of LS-TENG conjunct with CS-TENG and finger motion monitoring system based on CS-TENG. ga1 Highlights: The output performance of triboelectric nanogenerators is enhanced by using vertical contact-separation mode and lateral-sliding mode. The modification of PVA film with SnCl4 in friction layer significantly improves the power performance of the triboelectric nanogenerators. The proposed triboelectric nanogenerator is effectively used for multifunctional application of human motion monitoring.